Impacts of Water Quality, Fishing Mortality and Food Availability on the Striped Piggy Pomadasysstridens Production in Bitter Lakes, Egypt - Hoda Abd El-Azim; Sahar F Mehanna; Aisha A Belal (Annals of Marine Science - Peertechz Publications, 2017)
Pollution, fishing effort and food availability are the main factors affecting the fi sh production from natural resources. Bitter lakes are one of the important lakes in Egypt that produce a number of commercial species with mean annual fish production of 5000 ton. Recently a dramatic decline in this production is recorded and we try to find the main reasons for this. Water quality of the Bitter lakes and trace elements in the water and fish tissues were investigated during 2013. Five different sampling sites covering the whole course of the Bitter lakes were selected and pH, water temperature and salinity were measured. The cations Ca, Mg, Na, and K concentrations in sample water as well as the heavy metals Cu, Cr, Mn, Pb, and Cd in water and its residues in the tissues of Pomadasysstridens were determined. The crustacean communities as one of the main food items for P. stridens were studied in the chosen five sites. Density and diversity of marine crustaceans depend not only on the state of pollution but also on the type of substrates and different predators. The distribution of the crustaceans in the Bitter lakes varied widely within the different stations and seasons. A production model was applied to estimate some target reference points for the rational exploitation of P. stridens in Bitter lakes. The obtained results revealed that, the production depleting of this species is due to the overfishing and pollution that affect the food availability and the estimated precautionary target reference points advised the reduction of       fishing effort by about 40-55% as well as the treatment of pollution resources along the lakes.